PENGARUH KOMPETENSI SUPERVISI MANAJERIAL DAN MOTIVASI KERJA TERHADAP KINERJA PENGAWAS SEKOLAH DILINGKUNGAN DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA - Darto, K; Suib, Masluyah; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractCommon issues raised in this study is whether the competence of managerial supervision and motivation are equally affect the performance of the school superintendent in the Department of Education, Youth and Sports (Disdikpora) Sanggau. This study uses survey research with a quantitative approach. Data obtained from 60 samples of junior high school principal target supervisor in District Sanggau. The data collected by distributing questionnaires and were analyzed using multiple regression techniques. Results of correlation and regression analysis found a positive and significant influence between the competencies of managerial supervision, the motivation to work on the performance of the school superintendent in the Department of Education, Youth and Sports in Sanggau and there is positive and significant correlation between the competence of managerial supervision and motivation to work collectively equal to the performance of the school superintendent in the Department of Education, Youth and Sports in Sanggau.Keywords: Supervision Managerial Competence, Work Motivation and Performance School SupervisorÂ